MODIFIED S-CURVE MEMBERSHIP FUNCTION AND ITS APPLICATION TO FUZZY LINEAR PROGRAMMING (Journal of Information and Communication Technology, 2003)
The modern trend in industrial application problem deserves modeling of all relevant vague or fuzzy information involved in a real decision making problem. In this paper, the modified S-curve membership function and its methodology in solving real life problems are discussed. In the second part of the paper, the computation of fuzzy linear programming approach is made. Lastly, the usefulness of the modified S-curve membership function is established using a real life industrial production planning of a chocolate manufacturing unit. The unit produces 8 products using 8 raw materials, mix in various proportions by 9 different processes under 29 constraints. A solution to this problem is achieved, thus establishing the usefulness of the suggested membership function for decision making in maximizing objective function. From the theory and numerical results, it can be seen that the method presented here for solving a system of fuzzy mix product selection problem with modified S-curve membership function is very promising.